Upon a Stone Altar A History of the Island of Pohnpei to 1890 - Hanlon, David L. (Pacific Islands Monograph Series, 1988)
Upon a Stone Altar tells the history of a remarkable people who inhabit the island of Pohnpei in the Eastern Caroline Islands of Micronesia. Since the beginnings of intensive foreign contact, Pohnpei has endured numerous disruptive conflicts as well as attempts at colonial domination. Pohnpeians creatively adapted to change and today live successfully in a modern world not totally of their own making. Hanlon uses the vast body of oral tradition to relate the early history of Pohnpei, including the story of the building of a huge complex of artificial stone islets, Nan Madol.